Pesan Dakwah K.H Zulkifli Muhammad Ali dalam Ceramah di Youtube pada Akun UZMA Media TV Channel - Siti Rohimah; Saripuddin (Journal of Religion and Film, 2022)
This study used the library research method (literature research) which is explorative descriptive qualitative in nature. Qualitative research is concerned with non-numeric data, collecting and analyzing narrative data. Conducted on the YouTube channel "UZMA Media TV Channel" with data collection techniques using observation, literary data collection, namely digging library materials that are in the same direction as the object of study. And follow-up interviews to confirm the validity of the research. As a result, the researchers found that the figure of KH Zulkifli Muhammad Ali was a scholar from West Sumatra. By preaching through the media Da'wah Youtube using the mauidzoh hasanah method accompanied by blackboard explanations and a question and answer session such as following trends, that lectures no longer use a rigid method but only lecture with passive (listening) mad'u only. Besides that, using social media can help reach more mad'u and can be watched repeatedly. The material presented also specifically adds to the characteristics of the ustad. Ustad Zulkifli Muhammad Ali besides having talent in the world of da'wah also has an interest in the fifth pillar of faith, namely faith in the last day. With explanations that are in accordance with the Qur'an and Hadith, he also provides scientific facts so that mad'u understands and believes better that the Day of Judgment promised by Allah will come. Ustad Zulkifli conveyed material about the end times aimed at inviting people to prepare themselves and increase their acts of worship. Because only good deeds will save themselves from the slander of the end of time.